Socio-demographic influence on the pregnant women's comprehension of maternal health information in Tanzania - Emmanuel F. Elia; Jelly Ayungo (Heliyon, 2023)
Background: Pregnant women's understanding of maternal health information is critical in the application of information for pregnancy care, birth preparedness, and newborn care. However, the influence of socio-demographic characteristics on pregnant women's understanding of maternal health information is least understood. Purpose: The study examined the influence of social and demographic characteristics on pregnant women's comprehension of maternal health information. Methodology: A mixed research approach and descriptive cross-sectional design were applied. Questionnaires and focus group discussions were used to collect data from 132 pregnant women and 8 nurses/midwives. Data were analyzed using IBM SPSS version 21 and thematic analysis. Findings: Most of the pregnant women had a good ability to comprehend maternal health information. Level of education was found to influence the reading ability and language understanding ability of the pregnant women unlike age, marital status, income, and occupation. Age, level of education, monthly income, occupation, and marital status were found to influence the ability of pregnant women to understand maternal health information. Conclusion: The socio-demographic characteristics of pregnant women have an influence on their ability to comprehend maternal health information.